The impact on colostrum oxidative stress, cytokines, and immune cells composition after SARS-CoV-2 infection during pregnancy - Graciliano, Nayara Gomes; Tenório, Micaely Cristinados Santos; Fragoso, Marilene Brandão Tenório; Moura, Fabiana Andréa; Botelho, Rayane Martins; Tanabe, Eloiza Lopes Lira; Borbely, Karen Steponavicius Cruz; Borbely, Alexandre Urban; Oliveira, Alane Cabral Menezes; Goulart, Marília Oliveira Fonseca (Frontiers in Immunology, 2022)
Background Limited data are available regarding the differences between immunological, biochemical, and cellular contents of human colostrum following maternal infection during pregnancy with coronavirus 2 disease (COVID-19). Objective To investigate whether maternal COVID-19 infection may affect immunological, biochemical, and cellular contents of human colostrum. Methods Using a case-control study design, we collected colostrum from 14 lactating women with a previous diagnosis of COVID-19 during pregnancy and 12 without a clear diagnosis during September 2020 to May 2021. Colostrum samples were analysed for some enzymes and non-enzymatic oxidative stress markers (SOD, CAT, GPx, MDA, GSH, GSSG, H2O2, MPO) and for IL-1β, IL-6, tumour necrosis factor (TNF)-α, protein induced by interferon gamma (IP)-10, IL-8, IFN-λ1, IL12p70, IFN-α2, IFN-λ2/3, granulocyte macrophage colony stimulating factor (GM-CSF), IFN-β, IL-10 and IFN-γ, along with IgA and IgG for the SARS-CoV-2 S protein. We perform immunophenotyping to assess the frequency of different cell types in the colostrum. Results Colostrum from the COVID-19 symptomatic group in pregnancy contained reduced levels of H2O2, IFN-α2, and GM-CSF. This group had higher levels of GSH, and both NK cell subtypes CD3-CD56brightCD16-CD27+IFN-γ+ and CD3-CD56dimCD16+CD27- were also increased. Conclusion The present results reinforce the protective role of colostrum even in the case of mild SARS-Cov-2 infection, in addition to demonstrating how adaptive the composition of colostrum is after infections. It also supports the recommendation to encourage lactating women to continue breastfeeding after COVID-19 illness.